Faktor-faktor yang mempengaruhi Profitabilitas Perusahaan : Perputaran Modal Kerja, Perputaran Kas, Perputaran Persediaan, Perputaran Aset Tetap dan Perputaran Piutang - Denisa Salsabila Viyanis; Adira Oktaviani Tita Nurjanah; Khalisa Fahira; Avivah Shafa Nada; Tri Yulaeli (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Company Profitability is the company's ability to generate profit or profit. Profitability is the net result of various management policies and decisions. Profitability will provide the final answer about the effectiveness of company managers and provide an overview of the effectiveness of company management. Profitability can be interpreted as the company's ability to generate profits. According to R. Agus Sartono (2001: 122) profitability is the company's ability to earn profits in relation to sales, total assets and own capital. The company considers that the problem of profitability is more important regarding company profits, where companies that have large profits cannot reflect that the company operates efficiently. To assess the profitability of the company using solvency, current ratio and turnover receivables. This article reviews the factors that affect company profitability, namely: Working Capital Turnover, Cash Turnover, Inventory Turnover, Fixed Asset Turnover and Accounts Receivable Turnover in a study of financial management literature. The purpose of writing an article is to build a hypothesis on these variables so that they can be used for further research. The results of this review article are: Working Capital Turnover has an effect on Company Profitability, Cash Turnover has an effect on Company Profitability, Inventory Turnover has an effect on Company Profitability, Fixed Asset Turnover has an effect on Company Profitability and Accounts Receivable Turnover has an effect on Company Profitability